Assessing Dental Health Knowledge and Care Behavior Among School Children in Banjar City, Indonesia - Abigayl, Ivana; Putri, Antonietta Natasha (Dentistry Faculty, 2024)
Background: The prevalence of dental caries among school-aged children has been increasing annually, posing a significant public health concern. One of the key factors contributing to this issue is children's knowledge of oral and dental health. Poor oral hygiene and inadequate dental care knowledge are among the primary causes of oral health problems in children, leading to a higher risk of dental caries and other oral diseases. Objective: This study aims to examine the relationship between dental health knowledge and dental care behavior among school-aged children at SDN 1 Jajawar, Banjar City. Methods: A descriptive-analytical study with a cross-sectional design was conducted among fifth- and sixth-grade students aged 10 to 12 years at SDN 1 Jajawar. Data were collected using a structured questionnaire consisting of 36 items, designed to assess students' knowledge of dental health and dental care behaviors. Results: The findings revealed that 93.1% (n=54) of respondents demonstrated a low level of dental health knowledge and exhibited negative dental care behavior. This indicates a significant gap in awareness and practices related to oral hygiene among school-aged children. Conclusion: The study highlights the urgent need for enhanced education and intervention programs to improve children's knowledge of dental health and promote better oral hygiene practices. Strengthening oral health education at an early age is crucial in preventing dental caries and fostering lifelong positive dental care behaviors. Keywords: Dental caries, oral health knowledge, dental care behavior, school-aged children, oral hygiene, dental health education.